2000
DOI: 10.1055/s-0037-1613990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Eight Novel Single-Nucleotide Polymorphisms at Human Tissue-type Plasminogen Activator (t-PA) Locus: Association with Vascular t-PA Release In Vivo

Abstract: SummaryRecently, we reported that an Alu insertion polymorphism of the tissue-type plasminogen activator (t-PA) gene is associated with vascular t-PA release rates in man. In the current study we searched the t-PA gene for putative functional genetic variants in linkage disequilibrium (LD) with this polymorphism. Healthy individuals with different Alu genotypes and contrasting t-PA release rates were studied. Regulatory and coding regions of the t-PA gene were sequenced. Eight singlenucleotide polymorphisms (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
84
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(92 citation statements)
references
References 29 publications
5
84
3
Order By: Relevance
“…This process can probably explain spontaneous reperfusion in acute MI. In line with this hypothesis, it has been found that subjects carrying a variant of the t-PA gene with a low capacity for t-PA release are at greater risk of suffering a MI [4,5]. This finding was recently reproduced in the Framingham cohort [6].…”
Section: Introductionmentioning
confidence: 85%
“…This process can probably explain spontaneous reperfusion in acute MI. In line with this hypothesis, it has been found that subjects carrying a variant of the t-PA gene with a low capacity for t-PA release are at greater risk of suffering a MI [4,5]. This finding was recently reproduced in the Framingham cohort [6].…”
Section: Introductionmentioning
confidence: 85%
“…Eight novel polymorphisms were identified, 3 of which were in strong linkage disequilibrium with the Alu polymorphism and consequently, associated with t-PA release: Ϫ7351C/T in the upstream enhancer, 20 099T/C in exon 6, and 27 445T/A in intron 10. 70 The Ϫ7351 promoter polymorphism is located within an Sp1 binding site, whereas the coding region polymorphisms are silent. A population-based, prospective, case-control study found a Ͼ 2.5-fold increase in risk of MI among carriers of the Ϫ7531T allele, 71 which is in accordance with its reduced binding affinity to Sp1.…”
Section: Tissue-type Plasminogen Activatormentioning
confidence: 99%
“…By resequencing the promoter, the 3Ј untranslated region (3Ј-UTR), and all coding regions of the t-PA gene, 8 novel single-nucleotide polymorphisms (SNPs) were identified. 4 Three of these were associated with t-PA release: Ϫ7351CϾT, 20 099TϾC, and 27 445TϾA. The coding 20 099TϾC SNP is synonymous and the intronic 27 445TϾA SNP is not located in a splice site.…”
Section: Introductionmentioning
confidence: 99%